Produção artesanal de queijos: avaliação das condições de processamento, da qualidade higiênico sanitária e físico-química de queijos tipo coalho e manteiga - Medeiros, Jovilma Maria Soares de (2016)
The most popular type of cheese in the Seridó region are coalho and butter cheese, whose manufacturing process favors the microbial spoilage of such products and the variation in the composition thereof. Faced with the economic importance of these cheeses, aimed to evaluate the production conditions and the microbiological and physicochemical quality of coalho and butter cheese produced in the Seridó/RN region. To this end, we applied a checklist in five artisanal dairies, to evaluate the sanitary conditions in which these cheeses were produced, as it was also done training, the implementation of Good Manufacturing Practices and monitoring of corrective measures. Furthermore, we conducted microbiological testing for coliforms at 35 and 45°C in milk, cheese, water and utensils samples; total mesophilic bacteria in milk samples; Staphylococcus spp. In cheese and utensils samples; and Salmonella sp. In cheese samples, in total, there were 30 samples of each item analyzed at each dairy. Additionally, we carried out physicochemical analysis (humidity, ashes, lipids, pH, acidity, chlorides content and color) in five coalho cheese samples and in five butter cheese samples. The results showed a high percentage of non-conformities in all establishments analyzed. During the diagnosis the count of mesophilic bacteria in milk was higher than the recommended legislation, as well as coliforms at 35 ° C and 45 ° C in water samples. As for the coalho and butter cheese on both detected the presence of Salmonella sp. at diagnosis. High counts were also observed for the samples utensils. After the implementation of GMP in artisanal dairies observed increase in compliance percentages in items work environment hygiene and food handling , which resulted in the improvement of butter cheese processing conditions through significant reduction (p<0.05) coliforms at 35 °C and 45 °C. In this cheese as the coalho cheese, it observed absence of Salmonella sp. the samples after the implementation of GMP. On the subject of the physicochemical aspects, the chees samples showed variation of standards between the different producers in the same region, however they are within the parameters establishments by law. Given these results emphasize the importance of the implementation of Good Manufacturing Practices to improve the microbiological quality of artisan cheeses. What about the physical and chemical parameters was shown that the form of craft manufacturing while providing the preparation of cheeses with different constituents, ensures the compliance of these products with the legislation.